(3OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs - (3GdLRhdj, eMeO Hf SdjeGf Hf YHO GdQMef, J(B870(3g`s
(3ChdgG (B:s
(3bGd CHh YHO Gddg eMeO Hf SdjeGf GdLRhdj GdMeO ddg GdPj gOGfG ddEjeGfhHYO gPG aGdZQV aj gPG GdcJGH PcQ GdUdGI Ydi GdfHjhSejJg HcJGH OdGFd GdNjQGJs
(3BNQgG (B:s
(3Gddge HfhQ hLgc GdPj edC CQcGf YQTc Cf JRQY aj bdHj eYQaJc MJi CYQac Mb eYQaJc ceG jfHZj Cf JYQa Hg hUdi Gddg Ydi SjOfG hfHjfG hehdGfG eMeOs
(3aj BNQg LRA ef MRH GdfUQ ddTGPdj aj (B4 (3CSWQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 151s
(3eYLe GdeDdajf(B: 3 / 333s
(3cTa GdXfhf(B: 1 / 759s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs